Investigating the Situation of Social Development in the Provinces of the Country - Mehdi Mobaraki; zohreh shahbazi; Najme Mostafavi (توسعه اجتماعی, 2024)
Complexity and value judgments in social development have caused its model to appear ambiguous and distorted in many cases among experts. The absence of reliable and consensus social development has made monitoring a country’s social development process challenging. Besides, there is also a controversy over the reasons for choosing its social development. No clear definition of agreed-upon social development indicators to recognize the situation in time series has made the failure to evaluate programs and functions of institutions in charge a challenge for advancement in social development. The present study aims to achieve precise and agreed-upon definitions and situations of social development indicators according to the Iranian structural characteristics. as a result, the definitions of social development indicators were determined concerning the local conditions of Iranian society. While being close to international standards, the indicators made provincial, national, and international comparability possible and fixed the existing defects with their evolutionary features. The study employed exploratory sequential mixed methods instrument development design developed by Creswell and Plano Clark. First, international and domestic documents and reports on social development were examined, classified, and validated using the Delphi technique using Noblit and Hare’s meta-synthesis technique. Then, 107 indices were obtained through indexing, each evaluated and measured by secondary analysis in all Iranian provinces. As the results show, the mean scores of 19 provinces are lower than the national mean score. The distance between upper and lower provinces is significant in terms of average social development, and the pattern of social development in Iran is macrocephaly.